Desenvolvimento e aplicação de um aistema de análise por injeção em fluxo contínuo (FIA) para a determinação espectrofotométrica de fluoreto - Alvares, Antônio Carlos (2010)
The use of fluorine is closely related to the reduction the cariogenesis, and its action for this purpose is well known. The presence of the fluoride in different products of occasional use can lead to the excessive consumption of the fluorine and the emergence of human health problems such as fluorosis. The main goal of this present study was to develop a flow injection system, operating in reverse mode (injection of reagent instead of sample) for the rapid spectrophotometric determination of fluoride in different matrices. The method was based on the drifting of the Zr (IV), complexed by Zr-SPADNS (2 - (4 - sulphophenylazo) - 1,8 - dihydroxy - 3,6 naftaleneodisulphonic acid), by fluoride, which was the absorbing specie. All measurements were carried out at 595 nm and the FIA system was optimized in relation to the chemical and physical variables. Additionally, a study of the possible interferences was realized. The results obtained in the work showed that the concentrations of SPADNS and Zr (IV) affects both the sensitivity and the linear dynamic range of application of the method. At optimized conditions the SPADNS and Zr(IV) concentrations were 100 and 50 mg L-1, respectively. The limits of detection and quantification were 0.08 and 0.25 mg L 1, respectively. The sampling frequency, calculated from the time elapsed between two consecutive injections, was equal to 80 samples per hour. The method was applied for the determination of fluoride in solutions used for mouth cleaning and in the potable waters from Niterói and São Gonçalo cities.